2021
DOI: 10.3390/rs13245064
|View full text |Cite
|
Sign up to set email alerts
|

Testing Accuracy of Land Cover Classification Algorithms in the Qilian Mountains Based on GEE Cloud Platform

Abstract: The Qilian Mountains (QLM) are an important ecological barrier in western China. High-precision land cover data products are the basic data for accurately detecting and evaluating the ecological service functions of the QLM. In order to study the land cover in the QLM and performance of different remote sensing classification algorithms for land cover mapping based on the Google Earth Engine (GEE) cloud platform, the higher spatial resolution remote sensing images of Sentinel-1 and Sentinel-2; digital elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 60 publications
3
20
0
3
Order By: Relevance
“…In this study, we tested how different drone band combinations, referring both to single spectral bands and spectral indices can affect the classification results and which can be considered as the best combination resulting in higher thematic accuracy. According to the literature, existing studies have shown that the use of spectral indices can increase classification accuracy ( Phan, Kuch & Lehnert, 2020 ; Praticò et al, 2021 ; Yang et al, 2021 ). The spectral response of apicultural plants was estimated using six commonly used vegetation indices (Vis).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we tested how different drone band combinations, referring both to single spectral bands and spectral indices can affect the classification results and which can be considered as the best combination resulting in higher thematic accuracy. According to the literature, existing studies have shown that the use of spectral indices can increase classification accuracy ( Phan, Kuch & Lehnert, 2020 ; Praticò et al, 2021 ; Yang et al, 2021 ). The spectral response of apicultural plants was estimated using six commonly used vegetation indices (Vis).…”
Section: Methodsmentioning
confidence: 99%
“…Every decision tree would provide a cataloging choice utilizing the tool of numerous decision tree polling to fix the problem of easy decision tree overfitting and the widely held voting appliance policy to get the ultimate output (Paul et al, 2018;Wu et al, 2018). Some researchers have done significant work on the LU/LC grouping by using the algorithm of RF on the GEE stage, and the outcomes have been excellent (Zhang & Zhang, 2020;Yang et al, 2021;Phan et al, 2020). LULC types were done by directly calling the "ee.smileRandomForest function" from GEE of API, which merely necessities to know two parameters as the classification trees number and the feature variables number that entered at the node splitting time (Liu et al, 2020;Loukika et al, 2021).…”
Section: Random Forest Classifiermentioning
confidence: 99%
“…The most frequently used method to assess the classification performance of satellite images is a confusion matrix containing producer accuracy, consumer accuracy, overall accuracy and kappa coefficient (Yang et al, 2021;Basheer et al, 2022). The remaining 30% of the points (validation points) were applied to compute a confusion matrix comparing all three land-cover maps to their reference points (Basheer et al, 2022;Ochungo et al, 2022).…”
Section: Classification Of Satellite Images Covering Chitanga and Luidomentioning
confidence: 99%